Pengaruh Lingkungan Wirausahawan dan Pendidikan Kewirausahaan Terhadap Keberhasilan Usaha (Studi Kasus Pada Mahasiswa Administrasi Bisnis Angkatan 2016-2018) - Aulia Rehna Ramadhani (Universitas Muhammadiyah Ponorogo, 2021)
This study aims to examine and analyze the effect of entrepreneurial environment and entrepreneurship education on business success in students of the 2016-2018 FISIP UNMUL Business Administration. This type of research is quantitative research. This research method uses multiple linear regression analysis. Testing was carried out with the help of IBM SPSS version 22 software. The sample used in this study amounted to 38 respondents. The results of the F test (simultaneous) indicate that the entrepreneurial environment variables and entrepreneurship education have a significant effect on business success. The result of the t test (partial) shows that the entrepreneur's environment has a significant effect on the success of the business, while entrepreneurship education has no significant effect on the success of the business. The entrepreneurial environment is the variable that has the most dominant influence on the success of the business of the 2016-2018 FISIP UNMUL Business Administration students.Keywords: Entrepreneurial Environment, Entrepreneurship Education, Business Success